Penempatan Pemakaian Baju Kurung (Melayu) Pada Sekolah - Sekolah Di Kabupaten Bengkalis, Ditinjau Dari Sisi Moderasi Beragama - Husna Afriza; Siti Hawa (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
This article is the result of research from online media and several book references. To answer the problem regarding the placement of wearing baju kuning (Malay) in schools in the Bengkalis district in terms of religious moderation. The baju kuning is one of the traditional clothes of the Malay community, both in Indonesia, Brunei Darussalam, Malaysia, Singapore and southern Thailand. The baju kuning is often associated with traditional clothing because the traditional baju kuning is generally used for events related to custom, both for men and women. The use of traditional Malay baju kuning in the Riau region is supported by the Pekanbaru City Regional Regulation No. 12 of 2001 concerning the use of Malay clothing in the education environment for civil servants, private/regional-owned enterprises. The implementation of this regional regulation requires that students and employees in Riau wear special clothes in traditional Malay brackets on Fridays. In terms of religious moderation, in terms of religious moderation, the general public sometimes assumes that the Malay baju kuning is a religious identity. In fact, the Malay clothes in brackets are traditional clothes or traditional clothes from the Malay tribe in Riau. And they have a great sense of tolerance so there is no problem when they are advised to wear the baju kuning on Friday at schools where Muslims wear headscarves and caps while non-Muslims don't use them.